Back Cover: Artificial Cysteine S‐Glycosylation Induced by Per‐O‐Acetylated Unnatural Monosaccharides during Metabolic Glycan Labeling (Angew. Chem. Int. Ed. 7/2018). Issue 7 (16th January 2018) - Qin, Wei; Qin, Ke; Fan, Xinqi; Peng, Linghang; Hong, Weiyao; Zhu, Yuntao; Lv, Pinou; Du, Yifei; Huang, Rongbing; Han, Mengting; Cheng, Bo; Liu, Yuan; et al.
Abstract : Peracetylated unnatural sugars the "arrows" used by glycoscientists for decades to label cellular glycans, can induce artificial cysteine glycosylation on various proteins, as reported in the Communication onpage 1817 ff. by C. Wang, X. Chen et al. This "off‐targeting" of the per‐O‐acetylated sugar reporters can be likened to Cao Cao shooting arrows at scarecrows and straw boats in the fictitious story "Romance of the Three Kingdoms", and calls for caution in the use of peracetylated sugars and the development of better versions.